Membangun Aplikasi E-Commerce Berbasis Web Studi Kasus “PT. So Good Food Unit UHT” di Boyolali - Hendra Wahyu Saputra; Fariyono Fariyono; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2021)
PT SO GOOD FOOD UNIT UHT is a company engaged in the milk beverage business. Along with the development of the company, competition with other companies is becoming increasingly fierce, the credibility of the marketing system in terms of promotion and sales without limited reach is a determinant of the development of the company. So in this study, an online sales website (e-commerce) was created as a means of promotion and sale of Dairy Products offered by PT SO GOOD FOOD UNIT UHT and making it easier for customers to purchase products online. This website was built using the waterfall model, open-source programming tools based on PHP, MySQL database. The result achieved is an e-commerce website as a means of promotion and sales as well as making it easier for consumers to order products.